EKSTRAKSI DAN KARAKTERISASI EKSTRAK ZAT WARNA RUMPUT LAUT (Eucheuma cottonii) - Henny H. Veronika; Mappiratu Mappiratu; Ni Ketut Sumarni (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
This study was done for the following purposes: to found solution pH as an extract to result from an extract color substance with high concentration to found time of extraction which result extract with high concentration. Determination of the best eluent which can be used in the separation of pigmented compound from the extract, by using Thin Layer Chromatography (TLC) and determination of spectrum for each functional molecule. This study was done by a maceration-extraction method, determination of pH using phosphate buffer pH 5-6 and time of extraction during 1-4 hour, separation based on TLC and analysis FTIR spectrums. The result showed that ethanol extract of Eucheuma cottonii was contained the ficoeritrine compound. This extract has appeared brown yellow in acid solution and base solution with high absorbance at pH 9 and time extraction at 1 hour. Maximum absorbance from the extract was 330 nm and the best eluent in separation of this chemical by TLC preparation, it was mixture of Chloroform-Acetic Acid-Ethanol in composition of 30 : 15 : 2 (v/v/v), which indicating there were at least four compounds within the extract, two of these were coloring brown yellow and other two were colorless and it was free hydroxyl function and bind in hydrogen bound, also C=O function.Key words: Extraction, Eucheuma cottonii, buffer phospat, TLC.